Design and testing of a low-cost sensor and sampling platform for indoor air quality. (December 2021) - Tryner, Jessica; Phillips, Mollie; Quinn, Casey; Neymark, Gabe; Wilson, Ander; Jathar, Shantanu H.; Carter, Ellison; Volckens, John
Abstract: Americans spend most of their time indoors at home, but comprehensive characterization of in-home air pollution is limited by the cost and size of reference-quality monitors. We assembled small "Home Health Boxes" (HHBs) to measure indoor PM2.5, PM10, CO2, CO, NO2, and O3 concentrations using filter samplers and low-cost sensors. Nine HHBs were collocated with reference monitors in the kitchen of an occupied home in Fort Collins, Colorado, USA for 168 h while wildfire smoke impacted local air quality. When HHB data were interpreted using gas sensor manufacturers' calibrations, HHBs and reference monitors (a) categorized the level of each gaseous pollutant similarly (as either low, elevated, or high relative to air quality standards) and (b) both indicated that gas cooking burners were the dominant source of CO and NO2 pollution; however, HHB and reference O3 data were not correlated. When HHB gas sensor data were interpreted using linear mixed calibration models derived via collocation with reference monitors, root-mean-square error decreased for CO2 (from 408 to 58 ppm), CO (645 to 572 ppb), NO2 (22 to 14 ppb), and O3 (21 to 7 ppb); additionally, correlation between HHB and reference O3 data improved (Pearson's r increased from 0.02 to 0.75). Mean 168-h PM2.5 and PM10 concentrations derived from nine filter samples were 19.4 μg m −3 (6.1% relative standard deviation [RSD]) and 40.1 μg m −3 (7.6% RSD). The 168-h PM2.5 concentration was overestimated by PMS5003 sensors (median sensor/filter ratio = 1.7) and underestimated slightly by SPS30 sensors (median sensor/filter ratio = 0.91). Graphical abstract: Image 1 Highlights: We assembled a platform to sample/sense PM2.5, PM10, CO2, CO, NO2, and O3 indoors. Nine units were collocated with reference monitors in a home kitchen for one week. We tested manufacturer and empirical linear calibrations for low-cost gas sensors. Gas sensors correctly identified whether pollutants exceeded air quality guidelines. Cooking with natural gas burners led to 1-h indoor NO2 concentrations above 100 ppb.